A atuação profissional do professor nos anos iniciais do ensino fundamental e o sistema de avaliação da educação básica - Santos, Carolina Antonelli dos [UNESP] (2014)
The evalution system of Basic Education (Saeb) was introduced in Brazil in the 90s, as a public policy with the objective of monitor and contribute to the quality of education. In recent years, Saeb gained centrality in discussions about the quality of education, in terms of teacher's professional action against this pulicy evalution, developing their work in the classroom, which may or may not establish a relationship with guidelines set out by the reference matrix. Thus, the pedagogical practices of teachers can establish possible characteristics of independence or oscillation, the dimensions of Saeb, more particularly of topics and descriptions. This research aimed to investigate possible incidents of dimensions of evaluation systems on a large scale with the focus on Saeb, professional practice of teachers in the early years of basic education. The method of this study was divided into two phases. Phase 1 aimed to: promote contact with the particular teacher career paths, as well as the planning of Portuguese Language classes for the school year; obtain video recordings of lessions taught by the teacher, based on such records, discuss with the teacher on the dimensions Saeb (topics and descriptors), prioriziting the establishing of relations with the teaching practice of the teacher. This phase was divided into four stages. Phase 2 investigated whether and in that extension the conditions for interaction and discussion to which the teacher was exposed in Phase 1 would be linked with the performance of the teacher to teach new curriculum content for the same. This phase was divided into three stages. During data collection, interviews with the participanting teacher with performed with video recording (Phases 1 and 2), as well as observations and vídeo recordings of lessons taught by the participating teacher during this research (Phases 1 and 2). The results, in both phases of this study show evidence attesting interpretations of...